Copper(ii)-catalyzed protoboration of allenes in aqueous media and open air. (16th June 2020) - Snead, Russell F.; Nekvinda, Jan; Santos, Webster L.
Abstract : A copper(ii )-catalyzed internal protoboration of monosubstituted allenes efficiently occurs in water at room temperature and open air to generate 1, 1-disubstituted vinyl boronic acid derivatives. Abstract : A method has been developed for the facile Cu(ii )-catalyzed protoboration of monosubstituted allenes in aqueous media under atmospheric conditions. The reaction occurs site selectively, favoring internal alkene protoboration to afford 1, 1-disubstituted vinylboronic acid derivatives (up to 93 : 7) with modest to good yields. The method has been applied to a variety of phenylallene derivatives as well as alkyl-substituted allenes.